Driving effect of P16 methylation on telomerase reverse transcriptase-mediated immortalization and transformation of normal human fibroblasts - Xuehong Zhang; Paiyun Li; Ying Gan; Shengyan Xiang; Liankun Gu; Jing Zhou; Xiaorui Zhou; Peihuang Wu; Baozhen Zhang; Dajun Deng; Jing Ni (Chinese Medical Journal)
Abstract. Background:. P16 inactivation is frequently accompanied by telomerase reverse transcriptase (TERT) amplification in human cancer genomes. P16 inactivation by DNA methylation often occurs automatically during immortalization of normal cells by TERT. However, direct evidence remains to be obtained to support the causal effect of epigenetic changes, such as P16 methylation, on cancer development. This study aimed to provide experimental evidence that P16 methylation directly drives cancer development. Methods:. A zinc finger protein-based P16-specific DNA methyltransferase (P16-Dnmt) vector containing a “Tet-On” switch was used to induce extensive methylation of P16 CpG islands in normal human fibroblast CCD-18Co cells. Battery assays were used to evaluate cell immortalization and transformation throughout their lifespan. Cell subcloning and DNA barcoding were used to track the diversity of cell evolution. Results:. Leaking P16-Dnmt expression (without doxycycline-induction) could specifically inactivate P16 expression by DNA methylation. P16 methylation only promoted proliferation and prolonged lifespan but did not induce immortalization of CCD-18Co cells. Notably, cell immortalization, loss of contact inhibition, and anchorage-independent growth were always prevalent in P16-Dnmt&TERT cells, indicating cell transformation. In contrast, almost all TERT cells died in the replicative crisis. Only a few TERT cells recovered from the crisis, in which spontaneous P16 inactivation by DNA methylation occurred. Furthermore, the subclone formation capacity of P16-Dnmt&TERT cells was two-fold that of TERT cells. DNA barcoding analysis showed that the diversity of the P16-Dnmt&TERT cell population was much greater than that of the TERT cell population. Conclusion:. P16 methylation drives TERT-mediated immortalization and transformation of normal human cells that may contribute to cancer development.